Comparison of intranasal midazolam versus intravenous lorazepam for seizure termination and prevention of seizure clusters in the adult epilepsy monitoring unit - Owusu, Kent A.; Dhakar, Monica B.; Bautista, Cynthia; McKimmy, Dani; Cotugno, Stephanie; Sukumar, Nitin; Deng, Yanhong; Farooque, Pue; Hirsch, Lawrence J.; Maciel, Carolina B. (Epilepsy & behavior, 2019)
The objective of the study was to compare the performance of intravenous (IV) lorazepam (IVL) and intranasal midazolam (INM) for seizure termination and prevention of seizure clusters in adults admitted to the epilepsy monitoring unit (EMU) in whom seizures were captured on continuous video-electroencephalogram. Retrospective cohort of consecutive adults (≥18 years) with epilepsy admitted to the EMU at a single tertiary academic center, who experienced epileptic seizures (confirmed electroencephalographically) and required rescue therapy. The study spanned from January 2015 until December 2016, which included one year before and one year after transitioning from IVL to INM as the standard rescue therapy at our institution. A total of 50 subjects received rescue therapy and were included in the analysis. In the first year, out of 216 patients with epilepsy admitted to the EMU, 27 (13%) received IVL; in the second year, 23/217 (11%) received INM. There were no differences in baseline characteristics and markers of epilepsy severity, the median duration of index seizure (1.7 min [interquartile range (IQR): 1.1–2.7] in IVL vs. 2.0 min [IQR: 1.5–2.6] in INM group, p = 0.20), or in the number of subjects requiring repeat benzodiazepine administrations (IVL 8/27 [29.6%] vs. INM 7/23 [30.4%], p = 0.95). There were no differences in the median number of recurrent seizures in 24 h (1 [IQR: 1–3] in IVL vs. 2 [IQR: 1–4] in INM, p = 0.27), occurrence of status epilepticus (IVL 4/27 [14.8%] subjects vs. INM 1/23 [4.3%] subjects, p = 0.36), incidence of seizure clusters (IVL 8/27 [29.6%] subjects vs. INM 7/23 [30.4%] subjects, p = 0.95), need for transfer to an intensive care unit (ICU), or other adverse events. In our retrospective study, INM was comparable with IVL for seizure termination and prevention of seizure clusters in the adult EMU. Intranasal midazolam circumvents the need for IV access to be maintained throughout hospitalization and is an attractive alternative to IVL as a rescue therapy in this setting. Ideally, future large, prospective, randomized, and double blind studies are needed to confirm these findings. •Rapid penetration into the central nervous system is a critical feature for the efficacy of anti-seizure.•INM is an attractive option due to its rapid absorption and subsequent CNS delivery without the need for IV access.•Our results suggest that INM is comparable to IVL for the treatment of prolonged seizures in this setting.